2021
DOI: 10.1002/marc.202100100
|View full text |Cite
|
Sign up to set email alerts
|

3D Printable Conducting and Biocompatible PEDOT‐graft‐PLA Copolymers by Direct Ink Writing

Abstract: Tailor‐made polymers are needed to fully exploit the possibilities of additive manufacturing, constructing complex, and functional devices in areas such as bioelectronics. In this paper, the synthesis of a conducting and biocompatible graft copolymer which can be 3D printed using direct melting extrusion methods is shown. For this purpose, graft copolymers composed by conducting polymer poly(3,4‐ethylenedioxythiophene) (PEDOT) and a biocompatible polymer polylactide (PLA) are designed. The PEDOT‐g‐PLA copolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…It was found that the properties of the product could be tuned by the oligomer length, end group, and monomer composition with fine control (Spicer et al, 2017). In addition to the conductivity, the biocompatibility and non-toxicity of PEDOT are also deeply concerned by researchers (da Silva et al, 2018;Meng et al, 2019;Dominguez-Alfaro et al, 2021). In recent studies, a new type of conductive polymer-based biosensor has been obtained through monomer modification and polymerization (da Silva et al, 2018;Meng et al, 2020;Ritzau-Reid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the properties of the product could be tuned by the oligomer length, end group, and monomer composition with fine control (Spicer et al, 2017). In addition to the conductivity, the biocompatibility and non-toxicity of PEDOT are also deeply concerned by researchers (da Silva et al, 2018;Meng et al, 2019;Dominguez-Alfaro et al, 2021). In recent studies, a new type of conductive polymer-based biosensor has been obtained through monomer modification and polymerization (da Silva et al, 2018;Meng et al, 2020;Ritzau-Reid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-like structures made of cardiomyocytes with fibroblast were developed in PEDOT-g-PLA and cardiomyocyte, improving the approved suitable maturation and functionality of these cells. The promising results of the presented study could assist the progress of generating artificial tissue [108].…”
Section: Pla Applicationsmentioning
confidence: 74%
“…Interestingly, these scaffolds not only showed excellent biocompatibility properties in contact with cardiomyocytes and fibroblasts but also the formation of tissue-like structures composed of both cell lines ( Figure 3 a). 64 An innovative orthogonal photochemistry-assisted printing (OPAP) technique, combining extrusion printing and light-triggered chemistry, has been developed by Yu and co-workers for fabricating three-dimensional tough conductive hydrogels (TCHs) based on PEDOT and tyramine-modified poly(vinyl alcohol) (PVA-Ph). Ruthenium photochemistry was used to trigger two orthogonal photoreactions, a faster phenol-coupling reaction of PVA-Ph (∼27 s) and the polymerization of the conductive polymer precursors including 3,4-ethylenedioxythiophene (EDOT) (∼150 s), leading to a porous PVA hydrogel network with shorter PEDOT chains immobilized in the pores.…”
Section: Main Additive Manufacturing and 3d Printing Technologies Use...mentioning
confidence: 99%
“… (a) Biocompatible 3D scaffolds based on PEDOT- g -PLA for tissue engineering. Adapted and reprinted with permission from ref ( 64 ). Copyright 2021 Wiley-VCH GmbH.…”
Section: Main Additive Manufacturing and 3d Printing Technologies Use...mentioning
confidence: 99%